ANALYSIS OF RED ONION MARKETING IN RUBARU DISTRICT - SUMENEP DISTRICT - sugiarti, sugiarti; Kustiningsih, Nanik (Universitas Trunojoyo Madura, 2023)
The aim of this research is to analyze the marketing cycle, profits, efficiency and monopoly of shallots in the Rubaru area, Sumenep district. The data analysis method used in this research includes descriptive methods. To analyze the variables in this research, margin, efficiency and marketing monopoly formulas are used. The research results show that the shallot marketing channels in the Rubaru area, Sumenep Regency have the three highest marketing indicators, namely 3 marketing channels. The level of technical marketing efficiency in each shallot marketing channel, namely Channel I is IDR 125, Channel II is IDR 35.7 and Channel III is IDR 2.30. The monopoly of marketing institutions in Rubaru District, Sumenep Regency shows that there are still many third channel institutions that are ineffective, while second channel institutions are the most efficient.